PENGARUH MODEL CIRCUIT LEARNING BERBANTUAN MEDIA CARRD.CO TERHADAP HASIL BELAJAR KOGNITIF PENDIDIKAN PANCASILA - YULIYANTI, WULAN; JAMALUDIN, UJANG; BAHRUDIN, FEBRIAN ALWAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research was conducted in response to the results of field observations at SMA Negeri 5 Serang City, which still has minimal application of interactive learning models. Therefore, the students frequently experience boredom and lack enthusiasm for their studies. This study aimed to answer whether or not the circuit learning model assisted by Carrd.co media has an effect on cognitive learning outcomes of Pancasila Education. This study used a quasi-experimental method with a nonequivalent control group design, one type of quantitative research. A sample of 100 students, identified as class XI A1 (experimental) and XI S2 (control), were tested using pre-test and post-test. This showed the critical importance of selecting a suitable sample and a reliable and valid measurement instrument to guarantee that the research results accurately describe the effect of the learning model. A test technique was used to measure students' cognitive learning outcomes, with a pre-test and post-test instrument totaling 26 multiple-choice questions. The data analysis techniques utilized in this research included the normality test, homogeneity test, difference test (Wilcoxon test), hypothesis test (Mann-Whitney test), and n-gain test. The results of the analysis showed the value of Asymp. Sig (2-tailed) of 0.001 <0.05. Consequently, it can be inferred that the